Understanding the Interactions between Emissions Trading Systems and Renewable Energy Standards Using a Multi-Regional CGE Model of China - Fan, Ying (World Bank, Washington, DC, 2017)
Many countries have introduced policy measures, such as carbon pricing, greenhouse gas offsetting mechanisms, renewable energy standards, and energy efficiency improvements, to achieve their climate change mitigation targets. However, in many instances, these measures overlap in ways that may dilute each policy's greenhouse gas reduction potential. This study examines how a renewable energy standard in the power sector would interact with a national emission trading scheme that is introduced to achieve a greenhouse gas mitigation target. Using a static, multiregional computable general equilibrium model of China to simulate policy measures, the study finds that the addition of a separate renewable energy standard policy would increase the economic cost for achieving a target level of greenhouse gas mitigation. The study concludes that although renewable energy standard policies promote the use of renewable energies, they are an economic burden from the perspective of reducing greenhouse gas emissions if a carbon pricing mechanism is in place.